Toxine Botulique thérapeutique : Guide d'utilisation. - Truong, Daniel; Hallett, Mark.; Zachary, Christopher (Montrouge : DOIN, 2017)
La nouvelle édition du Manual of Botulinum Toxin TherapySpécialité par spécialité : les gestes et les particularités des traitements par la toxine botulique.
Print version record.
eBooks on EBSCOhost
Keywords: Botulinum toxin -- Therapeutic use; Toxines botuliniques -- Emploi en thérapeutique.; HEALTH & FITNESS -- Holism; HEALTH & FITNESS -- Reference; MEDICAL -- Alternative Medicine; MEDICAL -- Atlases; MEDICAL -- Essays; MEDICAL -- Family & General Practice; MEDICAL -- Holistic Medicine; MEDICAL -- Osteopathy; Botulinum toxin -- Therapeutic use